The Distribution of Income and the Marketing in the Bottom of the Pyramid - Shyle, Irma; Teta, Jonida (Mediterranean Journal of Social Sciences, 2012)
The world’s distribution of income, was been an ongoing concern for economists and scholars worldwide. Global incomeinequalities have also increased. Income inequalities exist for many reasons. Nowadays exist the big gap between the rich and the poorpeople. What is the definition of poverty? How many people in the world live in poverty? How poverty rates have changed over the lastfew decades? What is the situation of the poverty in Albania? Because of the global crises the number of the people that live with lessthan 2$ in days is growing faster than before. The population that are living with the less than 2 $ in day are identify as the bottom of thepyramid. The company cannot ignore the segment of the people that live with the less than 2 $ in day. This segment is becoming to beday by day bigger and to grow fast. For many international companies is important to adapt their strategies and their products to thatsegment. There are many businesses that do not truly understand the concept of the bottom of the pyramid. Though this market ismistakenly overlooked by many companies, the BOP segment is one that holds great potential for expansion and profits. Howcompanies can be successful in the bottom of the pyramid? The purpose of this paper is to review the existing literature on the BOP andput forth a set of principles that distinguish the BOP perspective from other poverty alleviation approaches.